Gene biotechnology - Wu, William; Zhang, Helen H.; Welsh, Michael J.; Kaufman, Peter B. (Boca Raton : CRC Press, 2011)
'The third edition of this popular reference covers a variety of techniques related to gene manipulation, including DNA isolation, preparation, screening, and analysis. Topics range from very basic methods to current and sophisticated technologies, including methodologies created and tested by the authors. Other topics include approaches to grant funding and SiRNA technology. The authors offer detailed, step-by-step explanations of protocols and helpful troubleshooting guides. This edition features new techniques for every chapter, as well as several new chapters'--Provided by publisher.
'A CRC title.'
Includes bibliographical references and index.
Keywords: Genetic engineering -- Laboratory manuals; Molecular biology -- Laboratory manuals